2022
DOI: 10.3390/ph15111367
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Solanum xanthocarpum Schrad. & Wendl. against Mycobacterium avium Subspecies paratuberculosis and Assessment of Its Immunomodulatory and Anti-Inflammatory Potential

Abstract: Mycobacterium avium subspecies paratuberculosis (MAP), being a dairy-borne pathogen, resistant of pasteurization and other sterilization techniques, is a major cause for development of inflammatory bowel disorders such as Johne’s disease (JD) in dairy animals and Crohn’s Disease (CD) in humans, for which no therapy is available to date. In the absence of effective therapy or a vaccine, management of CD has been accomplished by removal of the affected intestines. However, usually, even after removal of 2/3 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, even after 2/3 of the bowel segment has been removed, the remaining healthy bowel is usually re-involved, leading to disease recurrence. 47 Therefore, there is a need to develop an alternative therapy for this disordered flora infection. In recent years, researchers have begun to explore the use of gut microbiota vaccines for the treatment of IBD, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even after 2/3 of the bowel segment has been removed, the remaining healthy bowel is usually re-involved, leading to disease recurrence. 47 Therefore, there is a need to develop an alternative therapy for this disordered flora infection. In recent years, researchers have begun to explore the use of gut microbiota vaccines for the treatment of IBD, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Mycobacterium avium subspecies paratuberculosis (MAP) is a dairy-transmitted pathogen and a major cause of disease progression in IBD. 47 Although there is controversy regarding the possible causal relationship between CD and MAP, 48 several clinical trials have shown that selective anti-MAP drugs have been evaluated as a potential treatment for CD and found to be beneficial in terms of final outcome. In a study by Agrawal G et al a patient with CD could achieve profound mucosal healing after anti-MAP treatment alone.…”
Section: Resultsmentioning
confidence: 99%
“…Ayurveda and Unani natural therapies in particular have been utilised for many years as a treatment alternative for disorders associated with PSO ( Ramanunny et al, 2019 ). SX is frequently used to treat autoimmune and inflammatory diseases because of its potent anti-inflammatory and immunosuppressive characteristics ( Joghee, 2019 , Srivastava et al, 2022 ). SX consists of a variety of active phytochemical components that have an impact on several targets and pathways in the formation of PSO ( Parmar et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was also stated that seventy percent population depend upon the plants as source of their medicines. At present, a large number of traditional medicinal plants have been tested for their pharmacological activity against different diseases (Choudhary et al 2019;Srivastava et al 2022).…”
Section: Introductionmentioning
confidence: 99%